Problem-Solving Skill Based on Learning Independence Through Assistance in Independent Learning with Entrepreneurial-nuanced Modules - Amalia, Putri Rizki; Sukestiyarno, YL; Nur Cahyono, Adi (Unnes Journal of Mathematics Education Research, 2021)
This study aimed to describe the ability of problem solving in terms of the students’ learning independence with module-assisted independent learning. This research was conducted at MTs Negeri 1 Kudus 2019/2020 school year. The type of research used mix methods with concurrent embedded. The research data was taken by using questionnaire, observation, and test then processed by completeness test, comparative test, influence test, and improvement test. The results showed that the problem-solving ability was influenced by the students' learning independence. So independent learning by assisting students was able to make them to be more mature in science.